2022
DOI: 10.1111/jdv.18193
|View full text |Cite
|
Sign up to set email alerts
|

An integrated analysis of herpes virus infections from eight randomized clinical studies of baricitinib in adults with moderate‐to‐severe atopic dermatitis

Abstract: Background Atopic dermatitis (AD) is associated with an increased risk for viral infections including those caused by herpes simplex virus and varicella zoster virus. Objectives This study examined treatment‐emergent (TE) herpes simplex infection including eczema herpeticum (EH), and herpes zoster (HZ), in adult patients with AD receiving ≥1 dose of baricitinib (BARI), an oral selective inhibitor of Janus kinase 1/2. Methods We evaluated data from six double‐blinded, randomized, placebo‐controlled (PC) trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(71 reference statements)
0
7
0
3
Order By: Relevance
“…Factors such as impaired epidermal barrier function, chronic inflammation, and disturbed skin flora all contribute to increased viral susceptibility in AD patients. [18][19][20] Chronic eczematous lesions also present similar problems. This study found that CD2AP and CD123 specifically expressed in pDC were higher in chronic eczema lesions than in normal lesions, suggesting that pDCs accumulate in chronic eczema lesions, mainly in the superficial dermis and basal layer of the epidermis.…”
Section: Discussionmentioning
confidence: 95%
“…Factors such as impaired epidermal barrier function, chronic inflammation, and disturbed skin flora all contribute to increased viral susceptibility in AD patients. [18][19][20] Chronic eczematous lesions also present similar problems. This study found that CD2AP and CD123 specifically expressed in pDC were higher in chronic eczema lesions than in normal lesions, suggesting that pDCs accumulate in chronic eczema lesions, mainly in the superficial dermis and basal layer of the epidermis.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that the transformations that occur in the skin during senescence [ 3 ] and in some diseases, such as dermatoses [ 3 ], may increase the risk of infections that originate due to a virus [ 10 ], bacteria [ 11 ], and fungi [ 12 ]. In the present study, we demonstrated for the first time that hydrolyzed types I and III collagen importantly inhibited the inflammatory response induced by LPS in human fibroblasts (CCD-1072Sk) and human keratinocytes (hKT-nh-skp-KT0026).…”
Section: Discussionmentioning
confidence: 99%
“…Odds Ratio: 0,34; 95%‐Konfidenzintervall [KI]: 0,14–0,84, Eichenfield et al 11 . relatives Risiko: 0,31, 95% KI: 0,12–0,82) und keinen Einfluss auf die Rate systemischer Infektionen hat, führte die JAK‐Hemmung zu einem erhöhten Risiko vor allem von HSV‐Infektionen (in den Baricitinib‐Studien: Inzidenzrate von 2,0) 12–15 . Zu berücksichtigen ist, dass Patienten, die aufgrund ihrer Vorgeschichte ein erhöhtes Risiko für schwere HSV‐Infektionen hatten, in den Studien für JAK‐Inhibitoren ausgeschlossen wurden, in den EMA‐Zulassungen für die Behandlung der AD jedoch nicht exkludiert sind 12 …”
Section: Introductionunclassified
“…[12][13][14][15] Zu berücksichtigen ist, dass Patienten, die aufgrund ihrer Vorgeschichte ein erhöhtes Risiko für schwere HSV-Infektionen hatten, in den Studien für JAK-Inhibitoren ausgeschlossen wurden, in den EMA-Zulassungen für die Behandlung der AD jedoch nicht exkludiert sind. 12 Um dem Ziel einer patientenindividuellen Therapie näher zu kommen, wäre es hilfreich, AD-Patienten mit einem erhöhten Risiko für ein EH zu identifizieren. In früheren Arbeiten konnten wir zeigen, dass AD-Patienten mit einem EH in der Vorgeschichte eine erhöhte Frequenz an Typ-2-polarisierten virusspezifischen T-Zellen aufweisen.…”
Section: Introductionunclassified